Dual‐band high‐gain Fabry–Perot cavity antenna with a shared‐aperture FSS layer. Issue 13 (17th July 2018) - Chen, Jiaqing; Zhao, Yongjiu; Ge, Yue; Xing, Lei
Abstract : Here, a dual‐band high‐gain Fabry–Perot cavity antenna (FPCA) with a single superstrate layer is proposed. The design consists of a patch antenna and a double‐side frequency selective surface (FSS) superstrate. The unique feature of this design is to provide quasi‐optimal reflection phases with high reflectivity in two pre‐determined frequency ranges. To validate the design, a prototype is fabricated and measured. The experimental results indicate that peak gains of the FPCA achieve 10.1 and 15.2 dBi at 5.6 and 10 GHz, respectively. Moreover, compared with conventional dual‐band FPCAs, the proposed FPCA has a much smaller lateral size.